Hubungan Dukungan Suami Dengan Depresi Pascapersalinan pada Ibu Post partum - A.Dinda Putri Akikah; Andi Asrina; Andi Surahman Batara; Yusriani Yusriani; Fairus Prihatin Idris; Muh Ikhtiar (PT.Mantaya Idea Batara, 2026)
Introduction: Postpartum depression is a common emotional disorder that may adversely affect maternal well-being and child development. This study aimed to examine the relationship between social support and maternal characteristics and the likelihood of postpartum depression among mothers in the Batu Putih Community Health Center service area in 2025. A cross-sectional quantitative design was employed. The study participants were postpartum mothers residing in the Batu Putih Community Health Center service area. The independent variables included maternal age and the type of social support provided by husbands. The results showed no significant association between maternal age and the likelihood of postpartum depression (p > 0.05). In contrast, a significant association was found between husbands’ social support and the likelihood of postpartum depression (p < 0.05), with higher levels of support associated with a lower likelihood of postpartum depression. These findings indicate that social support, particularly from husbands, is a key factor influencing the likelihood of postpartum depression. Therefore, strengthening husbands’ involvement in preventive and promotive efforts is essential to reduce the risk of emotional disorders among postpartum mothers.